Probabilistic routing algorithm - Ta Hoang, Thuc Khanh (2014)
Over the years, several routing algorithms that select a routine from origin to destination has been studied. Route selection can be based on the route’s distance, ERP fare, or expected travel time based. Besides the purpose of getting a correct